Why are Indigenous Affairs Policies Framed in ways that Undermine Indigenous Health and Equity? Examining Australia’s Northern Territory Emergency Response - Freeman, Toby; Townsend, Belinda; Mackean, Tamara; Musolino, Connie; Friel, Sharon; McDermott, Dennis; Baum, Fran (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2022)
The 2007 Australian Northern Territory Emergency Response policy was harmful to the health of Aboriginal and Torres Strait Islander people. We thematically analysed 72 speech acts and reports from the three prominent perspectives: a Northern Territory government inquiry report, the Federal government, and an Aboriginal civil society coalition to examine how framings during the policy agenda setting phase constrained or supported scope for equitable health outcomes. The report authors and the coalition emphasised colonisation and other social determinants of Indigenous health. The Federal government used a discourse of pathology and white sovereignty. Our findings highlighted the need for Indigenous voice in policy making, and the need to address colonial assumptions underpinning policy framings to achieve Indigenous health equity.